To find \( f(-4) \) from the graph described, we first need to determine the equation of the line that passes through the points \( (0, 2) \) and \( (4, 0) \).
Let's find the slope \( m \) of the line using the slope formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Using the points \( (0, 2) \) and \( (4, 0) \):
\[ m = \frac{0 - 2}{4 - 0} = \frac{-2}{4} = -\frac{1}{2} \]
Now we have the slope. To find the equation of the line, we can use the point-slope form of the line equation:
\[ y - y_1 = m(x - x_1) \]
Using point \( (0, 2) \):
\[ y - 2 = -\frac{1}{2}(x - 0) \]
Simplifying gives:
\[ y - 2 = -\frac{1}{2}x \] \[ y = -\frac{1}{2}x + 2 \]
Now that we have the equation of the line \( f(x) = -\frac{1}{2}x + 2 \), we can find \( f(-4) \):
\[ f(-4) = -\frac{1}{2}(-4) + 2 \] \[ = 2 + 2 \] \[ = 4 \]
Thus, the value of \( f(-4) \) is:
\[ \boxed{4} \]